New Approach to Entrepreneurship Education in Primary Schools: the BGENTL - Paiva, Teresa (2018)
The European Union is promoting for more than 3 decades the entrepreneurship education in Europe, for all levels of education. One of the main goals is to strengthen the perspective of lifelong learning of the entrepreneurship education. So, the majority of the European countries are in a process of educational reform and are embedding this type of educational offering. Several methodologies are put in practice with different impact on entrepreneurship competences development and focusing in diverse subareas (e.g. creativity or business) and are applied at different levels of education. The primary level of education has specific characteristics and challenges, therefore different methodologies have to be applied. Early learning is always a motivation for acquiring behaviours and habits since learning modifies behaviour, cognitive, motor, sensory level, integrating changes in our values and attitudes. Mainly because most of the physical, emotional, psychosocial and cognitive changes occur during childhood and adolescence, projecting here, at this stage, the basis for a good self-esteem and selfconfidence. After an experience of implementing different methodologies and developing several projects, using games to promote learning is proven to achieve positive results in several areas of knowledge and behaviour. Therefore the proposal, here of a new methodology in entrepreneurship education for young children, the Board Game Entrepreneurship Learning (BGENTL) to promote entrepreneurship education to this student’s target, based on the use of different board games is appealing. Each one of the games has a specific purpose to develop specific areas related and that integrate what is called an entrepreneurship behaviour. In this paper, we’ll present the games and its several stages of this new methodology.